Quantification of acidic sites of nanoscopic hydroxylated magnesium fluorides by FTIR and 15N MAS NMR spectroscopy. Issue 109 (20th October 2015) - Hemmann, Felix; Agirrezabal-Telleria, Iker; Jaeger, Christian; Kemnitz, Erhard
Abstract : A new method is described for the calculation of molar extinction coefficients for quantitative FTIR measurements of acidic surface sites. Abstract : Lewis and Brønsted sites were quantified in a series of weak acidic hydroxylated magnesium fluorides by Fourier transform infrared spectroscopy (FTIR) and solid state nuclear magnetic resonance spectroscopy (NMR) with pyridine as probe molecule. Molar extinction coefficients, which are necessary for quantitative FTIR measurements, were calculated by an easy approach. It utilizes the fact that both signals, used for the quantification by FTIR, are caused by the same deformation vibration mode of pyridine. Comparison of quantitative FTIR experiments and quantification by NMR shows that concentrations of acidic sites determined by FTIR spectroscopy have to be interpreted with caution. Furthermore, it is shown that the transfer of molar extinction coefficients from one catalyst to another may lead to wrong results. Molar extinction coefficients and concentrations of acidic sites determined by FTIR spectroscopy are affected by grinding and probably the particle size of the sample. High temperature during FTIR experiments has further impact on the quantification results.